2021
DOI: 10.3390/ijerph181910263
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy Exposure, Aging Populations, and COVID-19: Considerations for Healthcare Providers and Public Health Practitioners in Africa

Abstract: Given the continent’s growing aging population and expanding prevalence of multimorbidity, polypharmacy is an increasingly dire threat to the health of persons living in Africa. The COVID-19 pandemic has only exacerbated these issues. Widespread misinformation, lack of vaccine access, and attempts to avoid being infected have resulted in increases in Africans’ willingness to take multiple prescription and nonprescription medications and supplements. Issues with counterfeit pharmaceuticals and the relatively ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Other studies have confirmed the rise in polypharmacy in adults with COVID-19. A study by Nwanaji-Enwerem et al Reported that in Africa, polypharmacy is a growing health threat as the population ages and the prevalence of several diseases increases, the effects of polypharmacy in Africa can be mitigated by strengthening training in evidence-based prescribing and joint decision-making [ 41 ]. Research works in previous epidemics have also shown that patients with polypharmacy are more likely to develop the disease and increase side effects [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have confirmed the rise in polypharmacy in adults with COVID-19. A study by Nwanaji-Enwerem et al Reported that in Africa, polypharmacy is a growing health threat as the population ages and the prevalence of several diseases increases, the effects of polypharmacy in Africa can be mitigated by strengthening training in evidence-based prescribing and joint decision-making [ 41 ]. Research works in previous epidemics have also shown that patients with polypharmacy are more likely to develop the disease and increase side effects [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of them opted for prescription refills rather than attending the FMC to receive their care. Some older people also use supplements to prevent COVID-19 infections, increasing the pill burden [ 26 ].…”
Section: Discussionmentioning
confidence: 99%